High-strength and high-porosity ceramic filter and preparation method thereof

By using the polystyrene ball template and gel molding molding process, the ceramic filter is prepared to solve the problem of decreased strength of ceramic filter when the pore rate is increased, and the ceramic filter with high strength and high porosity rate is achieved. Use efficiency and stability.

CN119371227APending Publication Date: 2025-01-28ZHENGZHOU UNIVERSITY OF AERONAUTICS
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411550832.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The strength of existing ceramic filters decreases sharply when the porosity increases, resulting in a decrease in usage efficiency and stability, and it is difficult to meet the requirements of melt flow characteristics of high-temperature alloys.

Method used

Use polystyrene balls as templates, forming molding process through gel molding, and prepare ceramic filters with regular pore structure and dense skeleton. By regulating the solid content of the slurry, sintering temperature and mold injection pressure, optimizing the pore rate and skeleton density density Essence

Benefits of technology

The high intensity and high pore rate of ceramic filters are realized, the stress concentration is avoided, the ability to resist pressure is improved, the service life is extended, and the flow characteristics of high -temperature alloy fuse are adapted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371227A_ABST
    Figure CN119371227A_ABST
Patent Text Reader

Abstract

The invention provides a high-strength and high-porosity ceramic filter and a preparation method thereof, and belongs to the field of ceramic filter materials. The preparation method comprises the following steps: firstly, preparing regularly arranged templates by adopting polystyrene spheres with equal diameters, then mixing Al2O3 powder, methacrylamide, N, N '-methylene bisacrylamide, ammonium citrate and deionized water, grinding into balls, then adding tetramethylethylenediamine, ethanol and ammonium persulfate to obtain slurry, finally pouring the slurry into a mold, applying a pressure, and finally, carrying out heat preservation for 2-4 hours, thereby obtaining the Al2O3 / Al2O3 composite material. And demolding, drying, degreasing and carrying out heat-preservation sintering treatment to obtain the high-strength and high-porosity ceramic filter. The prepared high-strength and high-porosity ceramic filter is uniform in pore size and pore distribution, the problem of stress concentration can be effectively solved, meanwhile, the framework structure is compact, large pressure can be borne, and high strength is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramic filter materials, and in particular to a high-strength and high-porosity ceramic filter and a preparation method thereof. Background Art

[0002] Among various methods of removing impurities, ceramic filters are widely used due to their excellent performance and ease of use. Ceramic filters have the characteristics of high porosity, large specific surface area, light weight, low thermal conductivity, and stable chemical properties. They can intercept larger particles of impurities, adsorb and intercept, filter out bubbles in molten metal, and adsorb fine impurities. They are widely used in metal casting, automobile exhaust treatment, etc.

[0003] The main methods for preparing ceramic filters include complex forming method, direct foaming method, sacrificial template method, 3D printing method, etc. The ceramic filters prepared by the above methods have problems such as loose skeleton structure and uneven pore size, which leads to low strength and affects its use. More seriously, when the porosity of the ceramic filter exceeds 70%, its strength drops sharply. In order to meet the use requirements, the porosity can usually only be reduced, sacrificing the filtration efficiency.

[0004] Chinese patent CN118341170A discloses a 3D printed ceramic filter and its forming method, which effectively prevents the casting liquid from vertically impacting the filter body components by setting the angle between the filter unit and the flow direction of the casting liquid less than 90° and providing a support frame in the filter unit, thereby improving the impact resistance of the filter body and making the filter less prone to damage. However, it only solves the problem that the filter pore size, shape, and distribution are uncontrollable and cannot match the flow characteristics of the high-temperature alloy melt.

[0005] Chinese patent CN117923944A discloses a method for preparing a composite ceramic filter, which uses BaZrO3 and Y2O3 as raw materials, adds dispersant and deionized water to make slurry, uses polyurethane foam with a pore size of 30-60PPI as a matrix, dip-coats the slurry on the matrix, and after drying, uses an in-situ decomposition carbon source method and high-temperature sintering to obtain the filter. The filter prepared by this method can resist the erosion of highly active melts, has better effects on small-sized inclusions, especially micron-sized inclusions, and can also automatically capture and adsorb Al2O3 non-metallic inclusions. However, the strength of the above-mentioned composite ceramic filter is relatively low.

[0006] Based on the above research, there are still many problems in preparing high-strength and high-porosity ceramic filters, especially solving the problem that the strength of ceramic filters decreases sharply as the porosity increases.

[0007] In summary, developing a new method for preparing foam ceramic filters, while maintaining high porosity, improving their strength by optimizing the pore structure, is of great significance to improving the efficiency and stability of ceramic filters and extending their service life. Summary of the invention

[0008] In view of this, the present invention provides a method for preparing a high-strength and high-porosity ceramic filter. The ceramic filter prepared by this method has uniform pore size and pore distribution, which can effectively solve the problem of stress concentration. At the same time, the skeleton structure is dense and can bear greater pressure, that is, obtain higher strength.

[0009] The method for preparing the high-strength and high-porosity ceramic filter of the present invention comprises the following steps:

[0010] (1) placing polystyrene balls of equal diameter into a mold to obtain a regularly arranged template;

[0011] (2) Al2O3 powder, ammonium methacrylamide, N,N'-methylenebisacrylamide, ammonium citrate and deionized water are mixed and added into a ball mill, and then Al2O3 grinding balls are added for ball milling for 20 to 24 hours. After the ball milling is completed, vacuum stirring is performed to degas, and then tetramethylethylenediamine, ethanol and ammonium persulfate are slowly added while magnetic stirring to obtain a slurry;

[0012] (3) pouring the slurry of step (2) into the mold of step (1) to completely fill the voids of the polyethylene template sphere, and applying pressure;

[0013] (4) after the slurry in step (3) solidifies, the pressure is removed and the mold is demolded, and after demolding, the mold is dried at room temperature to obtain a green body;

[0014] (5) placing the green body into a muffle furnace for degreasing to remove organic matter in the green body;

[0015] (6) The degreased green body is subjected to heat preservation and sintering to obtain the high-strength and high-porosity ceramic filter.

[0016] Preferably, the diameter of the polystyrene spheres in step (1) is 100 micrometers to 1 millimeter.

[0017] Preferably, the slurry in step (2) comprises the following raw materials in mass fractions:

[0018] Al2O3 powder 55%-76%, ammonium methacrylamide 3%-6%, N,N'-methylenebisacrylamide 0.3%-0.6%, ammonium citrate 0.3-0.4%, tetramethylethylenediamine 1-1.5%, ethanol 0.75-0.8%, ammonium persulfate 0.5-0.6%, and the rest is deionized water.

[0019] Preferably, in step (2), in order to prevent gelation due to excessive local concentration during addition, tetramethylethylenediamine is diluted to a volume fraction of 50% and ammonium persulfate is diluted to a mass fraction of 10% before use.

[0020] Preferably, the pressure in step (3) is 1-10 kgf / cm 2 .

[0021] Preferably, the solidification time in step (4) is 5 to 10 minutes, and natural drying is required for 20 to 24 hours after solidification.

[0022] Preferably, the drying time in step (4) is 60 to 72 hours.

[0023] Preferably, the specific method of degreasing in step (5) is: heating to 600° C. at a rate of 1 to 2° C. / min and keeping the temperature for 2 to 2.5 hours.

[0024] Preferably, the temperature of the sintering in step (6) is 1400-1650°C; the sintering time is 4-5h.

[0025] The present invention also provides a high-strength and high-porosity ceramic filter prepared by the method.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The present invention uses polystyrene balls as templates and utilizes its self-assembly characteristics to obtain a regularly arranged template with an opal structure. Then, a gel injection molding process is used to inject ceramic slurry into the above template to obtain a ceramic skeleton with an inverse opal structure, and a ceramic filter material can be obtained after final sintering. The ceramic filter prepared by this method has a regular pore structure (pore size, pore shape, pore distribution), and the pore size can be regulated according to the size of the polystyrene balls; the density of the skeleton can be regulated by the solid content of the slurry and the sintering temperature, and then its strength can be regulated; the window size and skeleton thickness between adjacent holes can be regulated by the pressure loaded during injection molding, and then the porosity can be adjusted, and finally a high-strength and high-porosity ceramic filter is prepared. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a picture of the ceramic multi-filter prepared in Example 2. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with the embodiments.

[0030] Example 1

[0031] A method for preparing a high-strength and high-porosity ceramic filter, comprising the following steps:

[0032] (1) Place polystyrene balls (1 mm in diameter) of equal diameter into the mold to obtain a regularly arranged template;

[0033] (2) Al2O3 powder, ammonium methacrylamide, N,N'-methylenebisacrylamide, ammonium citrate and deionized water are mixed and added into a ball mill, and then Al2O3 grinding balls are added at a rate of 2.5 times the mass of Al2O3 for ball milling for 24 hours. After the ball milling is completed, vacuum stirring is performed to degas, and then tetramethylethylenediamine, ethanol and ammonium persulfate are slowly added while magnetic stirring to obtain a slurry;

[0034] The mass fractions of the raw materials in the slurry are: 55% Al2O3 powder, 6% ammonium methacrylamide, 0.6% N,N'-methylenebisacrylamide, 0.3% ammonium citrate, 1% tetramethylethylenediamine, 0.75% ethanol, 0.58% ammonium persulfate, and the rest is deionized water;

[0035] To prevent gelation due to excessive local concentration during addition, dilute tetramethylethylenediamine to 50% by volume and ammonium persulfate to 10% by mass with some deionized water before use.

[0036] (3) Pour the slurry in step (2) into the mold in step (1) to completely fill the gaps in the polyethylene template ball and apply 1 kgf / cm 2 pressure;

[0037] (4) After the slurry in step (3) solidifies for 24 hours, the pressure is removed and the mold is demolded. After demolding, the mold is dried at room temperature for 72 hours to obtain a green body;

[0038] (5) placing the green body in a muffle furnace, heating it to 600° C. at a rate of 1° C. / min, and keeping it at that temperature for 2 hours to perform a degreasing treatment to remove organic matter in the green body;

[0039] (6) The degreased green body is sintered at 1400° C. for 4 h to obtain the high-strength and high-porosity ceramic filter.

[0040] The ceramic filter prepared in Example 1 has a porosity of 85%, a bending strength of 5 MPa, and a compressive strength of 5 MPa.

[0041] Example 2

[0042] A method for preparing a high-strength and high-porosity ceramic filter, the steps are as follows:

[0043] (1) placing polystyrene spheres (430 μm in diameter) of equal diameter into a mold to obtain a regularly arranged template;

[0044] (2) Al2O3 powder, ammonium methacrylamide, N,N'-methylenebisacrylamide, ammonium citrate and deionized water are mixed and added into a ball mill, and then Al2O3 grinding balls are added at a rate of 2.5 times the mass of Al2O3 for ball milling for 24 hours. After the ball milling is completed, vacuum stirring is performed to degas, and then tetramethylethylenediamine, ethanol and ammonium persulfate are slowly added while magnetic stirring to obtain a slurry;

[0045] The mass fractions of the raw materials in the slurry are: Al2O3 powder 76%, ammonium methacrylamide 3%, N,N'-methylenebisacrylamide 0.3%, ammonium citrate 0.3%, tetramethylethylenediamine 1%, ethanol 0.75%, ammonium persulfate 0.58%, and the rest is deionized water;

[0046] To prevent gelation due to excessive local concentration during addition, dilute tetramethylethylenediamine to 50% by volume and ammonium persulfate to 10% by mass with some deionized water before use.

[0047] (3) Pour the slurry in step (2) into the mold in step (1) to completely fill the voids of the polyethylene template ball and apply 4 kgf / cm 2 pressure;

[0048] (4) After the slurry in step (3) solidifies for 24 hours, the pressure is removed and the mold is demolded. After demolding, the mold is dried at room temperature for 72 hours to obtain a green body;

[0049] (5) placing the green body in a muffle furnace, heating it to 600° C. at a rate of 1° C. / min, and keeping it at that temperature for 2 hours to perform a degreasing treatment to remove organic matter in the green body;

[0050] (6) The degreased green body is sintered at 1650° C. for 4 h to obtain the high-strength and high-porosity ceramic filter.

[0051] The ceramic filter prepared in Example 2 has a porosity of 70%, a bending strength of 19 MPa, and a compressive strength of 28 MPa.

[0052] Figure 1 This is a picture of the ceramic multi-filter prepared in Example 2. Figure 1 (a) is the overall picture, Figure 1 (b) is a local image. Figure 1 It can be seen that the pore size is uniform, the pore shape is spherical, and the pore distribution is uniform and orderly, which will ensure its high strength. In addition, from its partial picture, it can be seen that the porosity of the ceramic filter is high, the skeleton thickness is uniform, and the pores are interconnected to form through holes, which ensures the high open porosity and high strength of the ceramic filter.

[0053] Example 3

[0054] A method for preparing a high-strength and high-porosity ceramic filter, comprising the following steps:

[0055] (1) Place polystyrene balls of equal diameter (100 μm in diameter) into a mold to obtain a regularly arranged template;

[0056] (2) Al2O3 powder, ammonium methacrylamide, N,N'-methylenebisacrylamide, ammonium citrate and deionized water are mixed and added into a ball mill, and then Al2O3 grinding balls are added at a rate of 2.5 times the mass of Al2O3 for ball milling for 24 hours. After the ball milling is completed, vacuum stirring is performed to degas, and then tetramethylethylenediamine, ethanol and ammonium persulfate are slowly added while magnetic stirring to obtain a slurry;

[0057] The mass fractions of the raw materials in the slurry are: 68% Al2O3 powder, 4.2% ammonium methacrylamide, 0.42% N,N'-methylenebisacrylamide, 0.3% ammonium citrate, 1% tetramethylethylenediamine, 0.75% ethanol, 0.58% ammonium persulfate, and the rest is deionized water;

[0058] To prevent gelation due to excessive local concentration during addition, dilute tetramethylethylenediamine to 50% by volume and ammonium persulfate to 10% by mass with some deionized water before use.

[0059] (3) Pour the slurry in step (2) into the mold in step (1) to completely fill the gaps in the polyethylene template ball, and apply 10 kgf / cm 2 pressure;

[0060] (4) After the slurry in step (3) solidifies for 24 hours, the pressure is removed and the mold is demolded. After demolding, the mold is dried at room temperature for 72 hours to obtain a green body;

[0061] (5) placing the green body in a muffle furnace, heating it to 600° C. at a rate of 1° C. / min, and keeping it at that temperature for 2 hours to perform a degreasing treatment to remove organic matter in the green body;

[0062] (6) The degreased green body is sintered at 1600° C. for 4 h to obtain the high-strength and high-porosity ceramic filter.

[0063] The ceramic filter prepared in Example 3 has a porosity of 75%, a bending strength of 10 MPa, and a compressive strength of 8 MPa.

[0064] Example 4

[0065] A method for preparing a high-strength and high-porosity ceramic filter, comprising the following steps:

[0066] (1) placing polystyrene spheres (750 μm in diameter) of equal diameter into a mold to obtain a regularly arranged template;

[0067] (2) Al2O3 powder, ammonium methacrylamide, N,N'-methylenebisacrylamide, ammonium citrate and deionized water are mixed and added into a ball mill, and then Al2O3 grinding balls are added at a rate of 2.5 times the mass of Al2O3 for ball milling for 24 hours. After the ball milling is completed, vacuum stirring is performed to degas, and then tetramethylethylenediamine, ethanol and ammonium persulfate are slowly added while magnetic stirring to obtain a slurry;

[0068] The mass fractions of the raw materials in the slurry are: Al2O3 powder 76%, ammonium methacrylamide 3%, N,N'-methylenebisacrylamide 0.3%, ammonium citrate 0.3%, tetramethylethylenediamine 1%, ethanol 0.75%, ammonium persulfate 0.58%, and the rest is deionized water;

[0069] To prevent gelation due to excessive local concentration during addition, dilute tetramethylethylenediamine to 50% by volume and ammonium persulfate to 10% by mass with some deionized water before use.

[0070] (3) Pour the slurry in step (2) into the mold in step (1) to completely fill the voids of the polyethylene template ball and apply 8kgf / cm 2 pressure;

[0071] (4) After the slurry in step (3) solidifies for 24 hours, the pressure is removed and the mold is demolded. After demolding, the mold is dried at room temperature for 72 hours to obtain a green body;

[0072] (5) placing the green body in a muffle furnace, heating it to 600° C. at a rate of 1° C. / min, and keeping it at that temperature for 2 hours to perform a degreasing treatment to remove organic matter in the green body;

[0073] (6) The degreased green body is sintered at 1650° C. for 4 h to obtain the high-strength and high-porosity ceramic filter.

[0074] The ceramic filter prepared in Example 4 has a porosity of 75%, a bending strength of 17 MPa, and a compressive strength of 23 MPa.

[0075] Comparative Example 1

[0076] A method for preparing a ceramic filter, the steps are the same as those of Example 2, except that the sintering temperature of Comparative Example 1 is 900°C.

[0077] The ceramic filter prepared in Comparative Example 1 had a porosity of 85%, a bending strength of 1.2 MPa, and a compressive strength of 0.6 MPa.

[0078] Comparative Example 2

[0079] A method for preparing a ceramic filter, the steps are the same as those of Example 2, except that the mass fractions of the raw materials in the slurry described in Comparative Example 2 are 85% Al2O3 powder, 3% ammonium methacrylamide, 0.3% N,N'-methylenebisacrylamide, 0.3% ammonium citrate, 1% tetramethylethylenediamine, 0.75% ethanol, 0.58% ammonium persulfate, and the rest is deionized water.

[0080] The ceramic filter prepared in Comparative Example 2 had a porosity of 82%, a bending strength of 2.9 MPa, and a compressive strength of 2.1 MPa.

[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high-strength and high-porosity ceramic filter, characterized in that: The following steps are involved: (1) Polystyrene balls of equal diameter are placed in a mold, and a regularly arranged template is obtained by mechanical vibration using its self-assembly characteristics; (2) Al2O3 powder, ammonium methacrylamide, N,N'-methylenebisacrylamide, ammonium citrate and deionized water are mixed and added into a ball mill, and then Al2O3 grinding balls are added for ball milling for 20 to 24 hours. After the ball milling is completed, vacuum stirring is performed to degas, and then tetramethylethylenediamine, ethanol and ammonium persulfate are slowly added while magnetic stirring to obtain a slurry; (3) pouring the slurry described in step (2) into the mold described in step (1) to completely fill the voids of the polyethylene template ball, and applying pressure; (4) after the slurry in step (3) solidifies, the pressure is removed and the mold is demolded, and after demolding, the mold is dried at room temperature to obtain a green body; (5) placing the green body into a muffle furnace for degreasing to remove organic matter in the green body; (6) The degreased green body is subjected to heat preservation and sintering to obtain the high-strength and high-porosity ceramic filter.

2. The method for preparing a high-strength and high-porosity ceramic filter according to claim 1, characterized in that: The diameter of the polystyrene spheres in step (1) is 100 micrometers to 1 millimeter.

3. The method for preparing a high-strength and high-porosity ceramic filter according to claim 1, characterized in that: The slurry in step (2) comprises the following raw materials by mass fraction: Al2O3 powder 55%-76%, ammonium methacrylamide 3%-6%, N,N'-methylenebisacrylamide 0.3%-0.6%, ammonium citrate 0.3-0.4%, tetramethylethylenediamine 1-1.5%, ethanol 0.75-0.8%, ammonium persulfate 0.5-0.6%, and the rest is deionized water.

4. The method for preparing a high-strength and high-porosity ceramic filter according to claim 1, characterized in that: The tetramethylethylenediamine in step (2) is diluted to a volume fraction of 50% before use, and the ammonium persulfate is diluted to a mass fraction of 10% before use.

5. The method for preparing a high-strength and high-porosity ceramic filter according to claim 1, characterized in that: The pressure in step (3) is 1-10 kgf / cm 2 .

6. The method for preparing a high-strength and high-porosity ceramic filter according to claim 1, characterized in that: The solidification time of step (4) is 5 to 10 minutes, and after solidification, it needs to be naturally dried for 20 to 24 hours before demoulding.

7. The method for preparing a high-strength and high-porosity ceramic filter according to claim 1, characterized in that: The drying time in step (4) is 60 to 72 hours.

8. The method for preparing a high-strength and high-porosity ceramic filter according to claim 1, characterized in that: The specific method of degreasing in step (5) is: heating to 600° C. at a rate of 1 to 2° C. / min and keeping the temperature for 2 to 2.5 hours.

9. The method for preparing a high-strength and high-porosity ceramic filter according to claim 1, characterized in that: The temperature of the heat preservation sintering in step (6) is 1400-1650° C., and the heat preservation sintering time is 4-5 hours.

10. A high-strength and high-porosity ceramic filter, characterized in that: The high-strength and high-porosity ceramic filter is prepared by the preparation method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation of ordered big hole porous ceramic film material

    CN101302117A

  • Method for preparing ceramic foams with pore gradient

    CN102093075A

  • Method for preparing porous ceramic heat-insulating material

    CN105884391A

  • Method for preparing ceramic filters with hot pressure casting process

    CN108178654A

  • Porous aluminum oxide ceramic and manufacturing method thereof

    CN110423135A